The birds (Aves) of Oromia, Ethiopia – an annotated checklist - Gedeon, Kai; Zewdie, Chemere; Töpfer, Till (European Journal of Taxonomy, 2017)
Oromia is the largest National Regional State of Ethiopia. Here we present the first comprehensive checklist of its birds. A total of 804 bird species has been recorded, 601 of them confirmed (443) or assumed (158) to be breeding birds. At least 561 are all-year residents (and 31 more potentially so), at least 73 are Afrotropical migrants and visitors (and 44 more potentially so), and 184 are Palaearctic migrants and visitors (and eight more potentially so). Three species are endemic to Oromia, 18 to Ethiopia and 43 to the Horn of Africa. 170 Oromia bird species are biome restricted: 57 to the Afrotropical Highlands biome, 95 to the Somali-Masai biome, and 18 to the Sudan-Guinea Savanna biome. 26 species of birds of Oromia are Threatened (three Critically Endangered, nine Endangered, and 14 Vulnerable), and an additional 20 species are classified as Near Threatened. International regulations affect 225 Ethiopian bird species. Of the polytypic species, a total of 620 subspecies can be taxonomically assigned to Oromia. 11 of them are endemic to Oromia, 71 to Ethiopia and 150 to the Horn of Africa. This very high diversity underlines the high responsibility of the Oromia National Regional State for bird conservation.